Enhancing Bone Repair: Impact of Raloxifene-Functionalized Cerabone® on Rat Calvarial Defects - Macedo, Laura Gabriela [UNESP] (2025)
Bone substitutes are commonly used in bone regeneration, and their functionalization with bioactive molecules can significantly enhance bone regeneration by directly influencing bone cells. This study aimed to evaluate the potential of raloxifene-functionalized Cerabone® (CB) for promoting bone repair and to highlight the implications in bone regeneration. The effectiveness of Cerabone® functionalized with raloxifene via sonication or gel delivery in promoting bone repair in rat calvaria defects was assessed. Ninety-six male rats with critical-sized calvarial defects were divided into six treatment groups (n = 16): COAG (spontaneous blood clot), CB (Cerabone®), CBS (Cerabone® sonicated alone), CBRS (Cerabone® with raloxifene sonicated), CBG (Cerabone® with gel vehicle), and CBRG (Cerabone® with 20% raloxifene gel). After 14 and 28 days, samples were analyzed using microtomography, histomorphometry, immunohistochemistry, and fluorescence techniques. Quantitative data were statistically analyzed, comparing each group to the control CB group with significance set at p < 0.05. Micro-CT analysis demonstrated a significant increase in bone volume in the CBRS, CBRG, and CBS groups at 28 days compared to the CB group (p < 0.05). Specifically, the mean bone volume percentages for the CBRS, CBRG, CBS, and CB groups were 21.18%, 17.51%, 13.18%, and 7.8%, respectively. Histomorphometry showed increased new bone formation in the CBRS and CBRG groups at both 14 and 28 days. Fluorescence analysis revealed a significantly higher daily mineral apposition rate in the CBRS and CBRG groups at 28 days. These findings suggest that raloxifene-functionalized CB, delivered via sonication or gel, significantly enhances bone repair by improving bone volume and mineralization, highlighting its potential as an effective strategy for bone regeneration.